Natural Occurrence, Biological Functions, and Analysis of D-Amino Acids - Gu, Shuang-Xi; Wang, Hai-Feng; Zhu, Yuan-Yuan; Chen, Fen-Er (Pharmaceutical Fronts, 2020)
This review covers the recent development on the natural occurrence, functional elucidations, and analysis of amino acids of the D (dextro) configuration. In the pharmaceutical field, amino acids are not only used directly as clinical drugs and nutriments, but also widely applied as starting materials, catalysts, or chiral ligands for the synthesis of active pharmaceutical ingredients. Earler belief hold that only L-amino acids exist in nature and D-amino acids were artificial products. However, increasing evidence indicates that D-amino acids are naturally occurring in living organisms including human beings, plants, and microorganisms, playing important roles in biological processes. While D-amino acids have similar physical and chemical characteristics with their respective L-enantiomers in an achiral measurement, the biological functions of D-amino acids are remarkably different from those of L-ones. With the rapid development of chiral analytical techniques for D-amino acids, studies on the existence, formation mechanisms, biological functions as well as relevant physiology and pathology of D-amino acids have achieved great progress; however, they are far from being sufficiently explored.
Keywords: D-amino acids; natural occurrence; biological functions; physiology; chiral analysis